2020
DOI: 10.3390/en13195152
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of New Anomaly Detection Technique for Wind Turbine Condition Monitoring Using Gearbox SCADA Data

Abstract: Anomaly detection for wind turbine condition monitoring is an active area of research within the wind energy operations and maintenance (O & M) community. In this paper three models were compared for multi-megawatt operational wind turbine SCADA data. The models used for comparison were One-Class Support Vector Machine (OCSVM), Isolation Forest (IF), and Elliptical Envelope (EE). Each of these were compared for the same fault, and tested under various different data configurations. IF and EE have not previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…A large selection of Machine Learning algorithms can also be used for anomaly detection. McKinnon et al have studied the performances in condition monitoring of a gearbox of three popular algorithms: Isolation Forest (IF), One Class Support Vector Machine (OCSVM) and Elliptical Envelope (EE) and found that depending on the conditions OCSVM and IF reach best results [ 33 ]. Purarjomandlangrudi et al used Support Vector Machine (SVM) to process previously extracted features of the data for early detection of anomalies [ 34 ].…”
Section: Previous Workmentioning
confidence: 99%
“…A large selection of Machine Learning algorithms can also be used for anomaly detection. McKinnon et al have studied the performances in condition monitoring of a gearbox of three popular algorithms: Isolation Forest (IF), One Class Support Vector Machine (OCSVM) and Elliptical Envelope (EE) and found that depending on the conditions OCSVM and IF reach best results [ 33 ]. Purarjomandlangrudi et al used Support Vector Machine (SVM) to process previously extracted features of the data for early detection of anomalies [ 34 ].…”
Section: Previous Workmentioning
confidence: 99%
“…One other use of Isolation Forest was presented by the authors of [51], where a comparison was made between Isolation Forest, One-Class Support Vector Machine, and Elliptical Envelope, for a condition monitoring technique for wind turbine SCADA data. That paper examined a novel technique that compared two months of data, separated by a year, for several turbines that failed due to a fault in the gearbox.…”
Section: Isolation Forestmentioning
confidence: 99%
“…It is believed that these effects would not last for 5 consecutive 10-min periods. This technique is illustrated in Figure 3 and also used in [51]. The number of anomalies detected is less relevant than the proportion of anomalies per window.…”
Section: Condition Monitoring Techniquementioning
confidence: 99%
“…Besides, some machine learning methods were applied to WT gearbox bearing condition monitoring 18 . McKinnon et al 19 presented support vector machine and isolation forest model to detect gearbox fault with SCADA data. Ruiming et al 20 combined with support vector regression (SVR), applied the corresponding relationship of the internal structure topology of WT and the observed SCADA data to detect faulty of the drive control system controller.…”
Section: Introductionmentioning
confidence: 99%